Development of double‐layer coupled coil for improving S/N in 7 T small‐animal MRI. Issue 5 (24th April 2015) - Kim, Kyoung‐Nam; Seo, Jeung‐Hoon; Han, Sang‐Doc; Heo, Phil; Im, Geun Ho; Lee, Jung Hee
Summary The purpose of this study was to develop a new double‐layer coupled (DLC) surface radiofrequency (RF) coil using a combination of single‐layer planar (SLP) and single‐layer circular (SLC) coils, for enhancement of magnetic flux (B1) sensitivity and RF penetration in 7 T rat‐body magnetic resonance imaging (MRI). The proposed DLC surface coil was fabricated according to an electromagnetic (EM) simulation and validated based on the B1 distribution and bench measurements. The DLC coil performance was quantitatively evaluated based on the signal‐to‐noise ratio (S/N) and coil–response signal intensity curves in phantom and in vivo rat‐body images. In the computational EM calculation and 7 T in vivo experimental results, the DLC surface coil clearly showed an increased S/N and higher RF transmit (B1+) profiles, compared to those of the SLP and SLC coils. While all surface coils displayed a rapid decrease in the MR signal from the near‐coil region to the subject, the results reveal that the DLC coil concept may be used to provide sufficient RF penetration and high S/N and degrees of freedom for use in partial body imaging for 7 T ultra‐high‐field small‐animal MRI. SCANNING 37:361–371, 2015. © 2015 Wiley Periodicals, Inc.